(3JgfFI Cgd GdESdGe HHfGA HjJ Gddg GdMQGes - (3Gdejehfj , EHQGgje Hf eMeO Hf YjSi, HQgGf GdOjf CHh ESMGb,J (B1079 (3g` s ((3efUhQ Hf Sdje Hf MSf GdOefGhi GdCRgQi s)
(3ChdgG (B:s
(3hbOQJg JYGdi eGRGdJ JQi YLjHkG hJHOi ZQjHkG CdN s
(3BNQgG (B:s
(3fSCd Gddg Cf jLeYfG Ydjg hjLPHfG Edjg Hefg hcQeg s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B103s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B518 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B124 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs